2008
DOI: 10.1002/pssr.200802003
|View full text |Cite
|
Sign up to set email alerts
|

Local chemical state change in Co–O resistance random access memory

Abstract: Kelvin probe force microscopy (KFM) and conductive atomic force microscopy (C‐AFM) together with micro X‐ray photoelectron spectroscopy (XPS) were performed for the stacking structure comprising of the transition metal oxide Co–O and metal electrode, which exhibits large reproducible resistance switching. The application of the external voltage by the C‐AFM cantilever decreases the resistance of Co–O, which well accords with the non‐polar forming process observed in the Pt/Co–O/Pt trilayer, known as the candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 11 publications
1
29
1
2
Order By: Relevance
“…Physical and chemical analyses of the filament by conventional analytical methods have therefore been hindered for a long time. Against this background, overcoming the above-mentioned difficulties by using conductive atomic force microscope (C-AFM) was reported to be possible [3,[5][6][7]. That is, by directly contacting transition metal oxide films with an AFM-tip and scanning the tip under application of dc bias voltage, a large area with an arbitrary resistance can be formed without a top electrode being deposited.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Physical and chemical analyses of the filament by conventional analytical methods have therefore been hindered for a long time. Against this background, overcoming the above-mentioned difficulties by using conductive atomic force microscope (C-AFM) was reported to be possible [3,[5][6][7]. That is, by directly contacting transition metal oxide films with an AFM-tip and scanning the tip under application of dc bias voltage, a large area with an arbitrary resistance can be formed without a top electrode being deposited.…”
Section: Introductionmentioning
confidence: 98%
“…However, the conductive filamentary paths, termed "filaments", are sandwiched between a top and bottom electrode. Moreover, it was reported that the diameter of the filaments is very small; some groups even reported the diameter to be less than 50 nm [3][4][5]. Physical and chemical analyses of the filament by conventional analytical methods have therefore been hindered for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts have been carried out using transmission electron microscopy [9, 10], atomic force microscopy [11] and other microscopy techniques to find experimental evidence that such switching behavior is caused by ion migration even at room temperature, through this ion transport is extremely slow at ambient temperatures. Now, atomistic pictures of the conducting path formation are becoming evident, supported by indirect observations for some devices to date, while most of the proposed models still include a certain amount of speculation.…”
Section: Introductionmentioning
confidence: 99%
“…One is oxygen vacancy nucleation at a metal/oxide interface. [8][9][10] Yang et al observed indirectly that oxygen vacancies are created and drift towards the cathode, forming localized conducting channels at Pt/TiO 2 /Pt cross-point junctions. 8 We observed the Pt electrode oxidization and oxygen vacancy formation at the interface of the Pt/HfO 2 /Pt system directly using hard x-ray photoelectron spectroscopy (HX-PES) under bias operation.…”
mentioning
confidence: 95%